Embriologia e ocorrência de fitomelanina em frutos de Wunderlichia senaeii (Glaz.) ex Maguire & G.M. Barroso (Asteraceae) - Moura, Ludimila Lemes (2015)
Basal groups of Asteraceae have controversial phylogeny. Mutisieae s.l. belong to these groups basal and is of great importance for the understanding of the phylogeny of the family. Embryological data are conservative and are known to have great potential for taxonomy. Therefore, they can provide important arguments that help to clarify the phylogenetic controversy in the family, especially in Mutisieae s.l. Thus, the embryological study Wunderlichia senaeii, a rare and endemic species of the region of Diamantina, Minas Gerais, was performed searching for features that help these clarifications. The material was collected and processed according to standard techniques of inclusion and microtomy. Anthers are tetrasporangiate biteca and the type of development of the anther wall is basic and the tapetum is secretory. The endothecium is fibrous with crystals. The microsporogenesis is successive and tetrads are tetrahedral. The pollen grain is twocelled. The ovary is inferior, bicarpelate, unilocular, with one anatropous ovule, tenuinucellate, unitegmic with basal placentation. The studied species has an obturator of funicular origin. The megagametophyte is the Polygonum type. The endosperm is cellular. The carpopodium is symmetrical and lignified. The cypsela has parenchymatous pericarp with phytomelanin deposition without forming schizogenous space. The exotesta has lignified thickening, the endosperm is persistent and surrounds the embryo with two plano-convex cotyledons. Some features found confirm the pattern of the family as the basic anther wall development, the secretory tapetum, fibrous endothecium, successive cytokinesis and tetrahedral tetrads. The ovary is inferior, bicarpellate, unilocular, with a anatropous ovule, tenuinucellate, unitegmic basal placentation and cellular endosperm. Other features like pollen grain bicelled and the obturator are rarely described for Asteraceae. The study also reports for the first time the presence of phytomelanin in basal species Asteraceae. This compound was previously only described for Heliantheae Alliance and the Heterocoma genus belonging to Vernonieae tribe.